Rethinking Funding Nonprofit Organizations Through Crowdfunding: The Use of Financial Technology (Asian Business Research, 2023)
This paper aims to examine the influence of FinTech, Crowdfunding, and Information Technology (IT) on Nonprofit Organizations (NPOs). The literature supported that NPOs increasingly utilize FinTech, Crowdfunding, and IT services to improve efficiency and effectiveness. Web-based Services and Technology Acceptance Model (TAM) are deployed to assess the impact of FinTech, Crowdfunding, and IT on NPOs. The TAM model was a valuable predictor of NPO acceptance and utilization of these technologies. The economic and social impact of innovative technology is significant. Fintech influences the development of digital transformation. Fintech offers alternative financing methods for nonprofit organizations through crowdfunding. By standardizing information, reducing transaction costs, and spreading the risk among several funders, online crowdfunding increase and diversify opportunities offered to donors.